Being cool or being good: researching mobile phones in Mozambique - Archambault, J (Anthropology Matters, 2009)
Drawing on my fieldwork experience in Inhambane, Southern Mozambique, where I conducted research on mobile phone use amongst youth, my paper tackles issues of acceptance and rejection. As I sought to gain acceptance amongst youth I found myself participating in various controversial and, at times, dangerous activities that made me the victim of intense gossip and outright rejection by some. The fact that I came to the field accompanied by my husband and daughter only made matters worse. In this paper, I present the challenges of “being cool”, while also “being good”, and the repercussions of my research choices on my social standing. I then discuss how, instead of compromising my research, this predicament had a positive outcome by revealing social dynamics that might otherwise have remained hidden, namely the importance of concealment and the ambiguous role mobile phones play in deceit.